0854 Camptocormia: what is the cause?. Issue 3 (9th February 2012) - Doherty, K M; Silveira-Moriyama, L; Nisbet, A; Noyce, A; Quinn, N; Parton, M; Lees, A J
Abstract : Camptocormia is a marked thoracolumbar flexion which occurs when a patient stands or walks. The underlying cause remains elusive in many, but it has been associated with muscle diseases and movement disorders. We present two patients. The first patient presented at age 70 with a history of becoming increasingly bent the further she walked, similar to her sister and father. She found walking upright uncomfortable and preferred to walk with her spine flexed to 90°. She was diagnosed with axial dystonia. On follow-up 5 years later she was able to walk erect by extending her arms behind her and locking her hands behind her back. She had mild weakness of deltoid and triceps. DNA analysis confirmed a diagnosis of facioscapulohumeral dystrophy (FSHD). The second patient was 57 years old when she developed a bent spine. She noticed she was only able to maintain a straight posture by holding onto a shopping trolley. She recalled her mother having a similar problem. Her CK was mildly raised. She was diagnosed with probable idiopathic axial dystonia. At 68 years old it was noted her eye closure could be overcome and she was slightly weak at both hip flexors. FSHD genetic testing was undertaken and was positive. Conclusion: (1) FSHD can present with localised weakness giving a classical camptocormia phenotype. (2) When presenting to movement disorder experts with a manoeuvre suggestive of a 'geste antagoniste', axial dystonia may be misdiagnosed. (3) The cause underlying camptocormia often remains undiagnosed. We propose a few subtle differences in the phenotypes of camptocormia due muscle disease, Parkinson's disease and dystonia which may help guide investigations.